The Effect of Cold Water Immersion on Arm Muscle Strength in the Basketball Team at SMA Negeri 3 of Malang City - Rizki Ramadhan; Widiawati, Prisca; Ramadhan, Muhammad Putra (Indonesian Journal of Sport Management, 2025)
Arm muscle strength is essential in basketball, especially in dribbling, shooting, and passing techniques. Therefore, to maintain good physical condition, it is necessary to also consider the recovery methods after training. The goal of this study is to determine the effect of cold water immersion on the arm muscle strength of the basketball team at SMA Negeri 3 of Malang City. This research utilizes an experimental study method. The design used in this research is the "One-group pretest-posttest design”. The results in the study showed that the women's basketball team received a significant value of 1.000 for the pull test and 0.802 for the push test, while the men's basketball team received a significant value of 0.042 for the pull test and 0.006 for the push test. Thus, it can be concluded that there is no effect of recovery using cold water immersion on the arm muscle strength of the female’s basketball team at SMA Negeri 3 of Malang City, but there is an effect of recovery using cold water immersion on the arm muscle strength of the male’s basketball team at SMA Negeri 3 of Malang City. This condition is caused by several factors, that is (1) hormonal differences between male and female athletes, (2) slower muscle adaptation in females, and (3) muscle size and composition.